Development control of coastal areas: a study on development control issues in Chenang Beach, Langkawi - Ngah, Kamarudin; Md Zan, Zainal; Abdul Rahman, Mohd Fitri; Mustaffa, Jamaludin; Ahmad, Zaim (Global Academic Excellence, 2018)
Urban land use regulation and control is the most important aspect of urban planning and urban geography and urban settlement studies. It is a method of controlling and planning the development of the area so that development plans made do not negatively impact on urban images, city developments, human settlements and the environment. Part III of the Town and Country Planning Act 1976 (Act 172), Amendment 2001 (Act A1129) has provided the need for the preparation of a development plan system as a development plan for a development area, whether at the state, district or special areas. This development plan consists of the State Structure Plan (RSN) covering the strategic planning of a state, District Local Plan (RTD) as a district development plan and Special Area Plan (RKK). These plans work to plan, control and guide development directions within its development area (Town and Country Planning Act 1976, Act 172). The study on coastal areas, Pantai Chenang, Langkawi, aims to assess issues related to development control which is increasingly serious and negatively affecting the population and the environment. The approach of the study is based on the principle of the spiraling research approach, using research methods on official / technical report sources, observation and interpretation of photographs. Analysis shows that among the identified issues are the threats of quality of sea and biodiversity threats, over capacity situations, land use conflicts, tourist and building safety, coastal exploitation and accessibility and circulation systems. Among the recommendations are the integrated accessibility and circulation system, rehabilitation and rehabilitation of seawater quality, coastal area development plans, land use distribution, planning control and development zones.